Program Bimbingan Belajar (BIMBEL) Matematika Untuk Siswa SD di Desa Semerap Pada Era Pandemi Covid-19 - Eline Yanty Putri Nasution; Decha Veronica (Politeknik Negeri Cilacap, 2022)
The covid-19 pandemic has caused schools to be temporarily closed to avoid crowds and avoid the spread of the coronavirus. That way, school activities continue to run even with online learning, Problems encountered in the community during the current covid-19 pandemic regarding online learning have resulted in a lack of enthusiasm for students to study independently at home without the assistance of a teacher, often the material being taught cannot be understood properly, and there is a decrease in learning achievement. Therefore, this community service activity provides and holds a Tutoring Program (BIMBEL) which aims to help students solve learning difficulties at school. That way, teaching and learning activities will be more efficient so that can be better and more optimal in developing their abilities. The activity was carried out using the face to face teaching method while still adhering to health protocols. The conclusions and results obtained from this program are that there is an increase in students learning enthusiasm and student learning outcomes both cognitively and skillfully.